Veliparib in Combination With Platinum-Based Chemotherapy for First-Line Treatment of Advanced Squamous Cell Lung Cancer: A Randomized, Multicenter Phase III Study. Issue 32 (10th November 2021) - Ramalingam, Suresh S.; Novello, Silvia; Guclu, Salih Zeki; Bentsion, Dmitry; Zvirbule, Zanete; Szilasi, Maria; Bernabe, Reyes; Syrigos, Konstantinos; Byers, Lauren Averett; Clingan, Philip; Bar, Jair; Vokes, Everett E.; et al.
Abstract : PURPOSE: Squamous non–small-cell lung cancer (sqNSCLC) is genetically complex with evidence of DNA damage. This phase III study investigated the efficacy and safety of poly (ADP-ribose) polymerase inhibitor veliparib in combination with conventional chemotherapy for advanced sqNSCLC (NCT02106546 ). PATIENTS AND METHODS: Patients age ≥ 18 years with untreated, advanced sqNSCLC were randomly assigned 1:1 to carboplatin and paclitaxel with veliparib 120 mg twice daily (twice a day) or placebo twice a day for up to six cycles. The primary end point was overall survival (OS) in the veliparib arm versus the control arm in current smokers, based on phase II findings. Archival tumor samples were provided for biomarker analysis using a 52-gene expression histology classifier (LP52). RESULTS: Overall, 970 patients were randomly assigned to carboplatin and paclitaxel plus either veliparib (n = 486) or placebo (n = 484); 57% were current smokers. There was no significant OS benefit with veliparib in current smokers, with median OS 11.9 versus 11.1 months (hazard ratio [HR], 0.905; 95% CI, 0.744 to 1.101; P = .266). In the overall population, OS favored veliparib; median OS was 12.2 versus 11.2 months (HR, 0.853; 95% CI, 0.747 to 0.974), with no difference in progression-free survival (median 5.6 months per arm). In patients with biomarker-evaluable tumor samples (n = 360), OS favored veliparib in the LP52-positive population (median 14.0 v 9.6 months; HR, 0.66; 95% CI, 0.49 to 0.89), but favored placebo in the LP52-negative population (median 11.0 v 14.4 months; HR, 1.33; 95% CI, 0.95 to 1.86). No new safety signals were observed in the experimental arm. CONCLUSION: In current smokers with advanced sqNSCLC, there was no therapeutic benefit of adding veliparib to first-line chemotherapy. The LP52 signature may identify a subgroup of patients likely to derive benefit from veliparib with chemotherapy.